2006
DOI: 10.1590/s0100-40422006000600027
|View full text |Cite
|
Sign up to set email alerts
|

Principais métodos de síntese de amidinas

Abstract: Recebido em 8/6/05; aceito em 6/1/06; publicado na web em 6/7/06 SYNTHETIC APPROACHES TO AMIDINES. The amidine functional group is found in a wide range of natural products and is biologically active against several pathogens. In addition, amidines have long been regarded as useful intermediates in the synthesis of heterocyclic compounds. Consequently, a great number of methods have been developed for the preparation of amidines. Pinner's method is the most commonly used. Conventional methods include: -the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Regarding SAXA degradation process, reactions (Equations (10)–(12)) were constructed, based on specific available literature [16,30,31], amidine, epimer, and formyl amide formation mechanisms [19,32,33,34,35,36,37] and own experimental measurements. Jones et al identified solvent’s propensity to participate in proton transfer and ESCA autocatalysis as the two main contributors of SAXA to ESCA conversion [16]; however, to our set of solid-state reactions, this does not directly apply, owing to slower reaction rates and specific micro-environmental conditions, established by tablet excipients.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding SAXA degradation process, reactions (Equations (10)–(12)) were constructed, based on specific available literature [16,30,31], amidine, epimer, and formyl amide formation mechanisms [19,32,33,34,35,36,37] and own experimental measurements. Jones et al identified solvent’s propensity to participate in proton transfer and ESCA autocatalysis as the two main contributors of SAXA to ESCA conversion [16]; however, to our set of solid-state reactions, this does not directly apply, owing to slower reaction rates and specific micro-environmental conditions, established by tablet excipients.…”
Section: Resultsmentioning
confidence: 99%
“…Although the significant number of synthetic routes into discrete amidines have been reviewed elsewhere , amidine‐based isologs of Arg have been prepared as discrete compounds through a variety of different means, including various iterations of standard Pinner syntheses of nitrile substrates , condensation of alkyl acetimidates with the δ‐amine of appropriately functionalized Orn precursors , and treatment of Orn δ‐thioamides with ammonia . Overwhelmingly, the final product in these syntheses has been the discrete Arg isologs themselves, without their incorporation into larger peptides.…”
Section: Introductionmentioning
confidence: 99%